Interdisciplinary Assessment of Market Oriented Yam Cultivation in Semi-arid Burkina Faso - Heller, Olivier; Kiba, Delwendé I.; Zida, Kalifa Wend-Doléa; Schneider, Kim; Valérie Kouame, Hgazat Kouassi; Traoré, Ouakoltio Y. A.; Siegrist, Michael; Frossard, Emmanuel (Frontiers in Agronomy, 2022)
Yam (Discorea spp.) is a staple food crop in Africa that requires fertile soils and an annual rainfall of about 1,500 mm. However, in the semi-arid North-West of Burkina Faso, farmers produce yam in continuous rotation on degraded soils with annual rainfall of 610–960 mm. Understanding this local know-how can help improve yam cultivation in other regions and cropping systems in Africa. This study evaluated the productivity of this yam farming system in an interdisciplinary manner involving agronomic and economic analyses. We studied the cropping practices and socio-economic conditions of 67 households in 12 villages. We questioned farmers about their yam management schedule and inputs and we measured the yam fresh tuber yields in their fields. We sampled soils, manure and yam tubers for chemical analyses. Then, we calculated soil surface nutrient balances for N, P, and K. We found that the cropping system was characterized by densely planted ridges and relatively small size of harvested tubers. The farmers coped with degrading soils and increasing market demand by applying in average 16.2 t ha−1 of manure. About 31% of the farmers applied an average of 435 kg ha−1 of NPK fertilizer and another 24% applied an average of 300 kg ha−1 of urea. The average yam yield was 16.2 t ha−1, well above the West African average yield of 10.7 t ha−1.The yam had high value (0.59 USD kg−1) at relatively low production expenditure (0.04 USD kg−1), providing farmers the opportunity to increase and diversify incomes. Our results suggest that the development of this intensified yam production may be limited by farmer's low purchasing power of yam seed tubers, fertilizers and labor.